Cogging Torque Reduction and Offset of Dual-Rotor Interior Permanent Magnet Motor in Electric Vehicle Traction Platforms - Myeong-Hwan Hwang; Hae-Sol Lee; Se-Hyeon Yang; Gye-Seong Lee; Jong-Ho Han; Dong-Hyun Kim; Hyeon-Woo Kim; Hyun-Rok Cha (Energies, 2019)
Recently, various methods have been proposed to increase the output power density of a driving motor applied to an electric vehicle. One such method is to design a structure with two motor rotors. High output density can be obtained by applying the dual rotor to the motor. However, this increases the cogging torque, which can cause high noise and vibration. In this paper, we proposed a method for reducing the cogging torque by adjusting the angle between the magnet and the dual rotor, as well as a novel method for reducing the cogging torque by angular adjustment of the slot opening based on electromagnetic field analysis. In addition, the design was implemented by applying a split core to increase the ease of manufacturing and the dot rate in the motor. We believe that high cogging torque, which is a disadvantage of dual rotor motors, can be lowered by the methods proposed in this paper. The results of this study are expected to be applicable to electric vehicles that require high output power density.